Association Between PAI-1 4G/5G Genetic Polymorphism and Uncontrolled Allergic Asthma - Harun Iskandar; Muh Ilyas; Eliana Muis; Nur Ahmad Tabri; Dewi Setiawati (Advance Sustainable Science Engineering and Technology, 2025)
Airway remodeling is a major challenge in the management of uncontrolled allergic asthma, despite standard therapy with a combination of inhaled corticosteroids (ICS) and long-acting bronchodilators (LABA). Increased levels of Plasminogen Activator Inhibitor-1 (PAI-1) are thought to play a role in this process, and the 4G/5G polymorphism in the PAI-1 gene is one of the genetic factors that affect it. This study aimed to analyze the association between the 4G/5G PAI-1 genetic polymorphism and uncontrolled allergic asthma. A case-control study was conducted at Wahidin Sudirohusodo General Hospital between January-March 2024 on 40 patients with allergic asthma and 40 non-asthmatic subjects. Diagnosis was made through prik test (+), bronchodilator test (+), and asthma control classification according to GINA criteria. All asthmatic patients received Budesonide-Formoterol therapy for 4 weeks. PAI-1 levels were measured and 4G/5G polymorphism was analyzed by RT-PCR. Results showed that PAI-1 levels were significantly higher in uncontrolled asthma patients and in individuals with the 4G/4G genotype compared to non-4G/4G (2.38 ± 0.770 vs 1.65 ± 0.714; p=0.001). The 4G/4G genotype was more common in uncontrolled asthma (OR: 5.8) and was associated with the risk of severe obstruction (OR: 11.6). Thus, it was concluded that the 4G/4G genotype in the PAI-1 gene is associated with increased PAI-1 levels, risk of uncontrolled allergic asthma, and more severe degree of airway obstruction. The implication of the results shows that genetic testing of PAI-1 has the potential to be a predictive biomarker in personalized asthma therapy strategies. This approach can help clinicians identify high-risk patients and tailor interventions early and effectively to prevent remodeling and reduce long-term morbidity.